Effects of Urban Characteristics on Traffic Accidents - Al-Masaeid, Hashem R.; AL-Tal, Raed S.; Mahmoud, Muna A. (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study aimed to examine the effects of urban planning, road network, and other urban related characteristics on road traffic accidents. Amman, the capital of Jordan, which consists of 22 urban districts, was taken as a case study. A cross-sectional data on traffic accidents of different types, urban planning, road network, passenger- and vehicle-kilometers of travel, public transport accessibility, and topographic characteristics were collected. Multivariate regression analyses were performed to develop statistical relationships that may help city planners and traffic engineers to set safety policies and regulations for safe urban environment. The results of analyses indicated that the increase in vehicle-kilometers of travel, road and intersection densities, and percentage of mixed land-use were significantly increasing all types of accidents in each urban district. Also, the results indicated that population density, availability of public transit lines along primary and collector streets, accessibility to public transit services, and school density were significantly related to the pedestrian accident density.